Pengaruh Program Jaminan Hari Tua BPJS Ketenagakerjaan terhadap Kesejahteraan Finansial Pekerja Bukan Penerima Upah pada Kantor Cabang BPJS Ketenagakerjaan Lima Puluh Kota - Anisa Ramadani; Novera Martilova (Lembaga Yasin AlSys, 2026)
Employment social security programs, particularly the Old-Age Security Program (JHT), have received attention in various previous studies; however, studies that specifically examine their effect on the financial well-being of non-wage workers (BPU) at the local level remain limited. This study aimed to analyze the effect of the JHT program on the financial well-being of BPU workers in Lima Puluh Kota Regency. This study used a quantitative approach with a survey design. The research respondents were BPU workers selected through purposive sampling. Data were collected using a questionnaire that had been tested for validity and reliability, and were then analyzed using simple linear regression with the assistance of SPSS. The results showed that the JHT program had a significant effect on financial well-being, as indicated by a calculated t-value of 4.294, which was greater than the t-table value of 1.997, with a significance level of 0.000 < 0.005. However, the contribution of the JHT program to financial well-being was relatively limited, as shown by a coefficient of determination of 22.1%. These findings indicate that the financial well-being of BPU workers is also influenced by factors beyond the JHT program. This study contributes to the development of studies on financial well-being and life-cycle theory, while also expanding understanding of the role of social security in the context of informal sector workers. The implications of this study emphasize the importance of optimizing the JHT program, improving social security literacy, and strengthening the participation of BPU workers as efforts to support more sustainable financial well-being.